Haji Jalan Kaki: Representasi Sosial dan Dramaturgi Spiritualitas di Media Sosial - M Shufiadin (Yayasan Salam Cerdas Al-Fattah, 2025)
The phenomenon of Hajj on foot, which has recently been in the public spotlight on social media, has led to debates in the public sphere regarding the meaning, motivation, and authenticity of the practice. This research uses a qualitative approach with phenomenological methods to understand how people interpret the phenomenon. Primary data was obtained through in-depth interviews with religious leaders, people who are pro and contra to this phenomenon, as well as secondary data in the form of book and journal literature. The analysis technique uses Serge Moscovici's Social Representation theory and Erving Goffman's Dramaturgy theory. The results showed that: (1) The community forms polarized social representations, some of which consider it a form of high spirituality, while others consider it a practice of riya or seeking benefits (gifts); (2) Social media functions as a front stage where Hajj Walking actors manage their religious narratives and images, which are displayed in the form of vlogs, photos, and live streaming; (3) There is a gap between what is displayed on the front stage and more complex motivations or goals in the backstage, giving rise to controversy in society. This study concludes that in the digital era, religious practices are not only a matter of personal faith, but also social representations that are dynamically constructed and exchanged in the public sphere. This requires people to be more critical and reflective in understanding contemporary spirituality.